The 3rd Annual Conference on " The Image of an African Politician and a Public servant in the 21st century" - Sebola, M. P. (editor); Tsheola, J. P. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
Refer to the document
Conference proceedings (80 articles)
Keywords: African politician; Public servant; Civil service; Civil service -- Political activity; Politicians -- Africa; Civil servants -- Africa; Africa -- Official and employees -- Political activity